Literature Review: Health Promotion Strategies Stunting Prevention in Timor-Leste - Cruz Menezes da Silva, Ines da; Auxiliadora Menezes da Silva, Dircia; Maria Ximenes, Herminia; Jesus Vaz Cabral, Teresa de; Santos Ximenes, Herminia dos (Rifa'Institute, 2024)
Stunting remains a critical public health issue in Timor-Leste, significantly impacting child development and future societal progress. This literature review examines various health promotion strategies aimed at preventing stunting in the country. By analyzing key studies and intervention programs, this review highlights effective approaches, including community-based nutrition education, maternal health improvement, and government-led initiatives. The role of public awareness campaigns and the integration of healthcare services also emerge as essential components in tackling stunting. The findings suggest that a multi-sectoral and culturally sensitive approach is critical for the long-term success of stunting prevention efforts in Timor-Leste. Future recommendations emphasize the need for sustained political commitment and enhanced resource allocation to ensure the sustainability of these health promotion strategies.